Against Sex Education Pedagogy, Sex Work, and State Violence - Howlett, Caitlin (Radical Politics and Education, 2021)
This book is available as open access through the Bloomsbury Open programme and is available on www.bloomsburycollections.com. Why do we have sex education? For whom does it exist, and who is it against? This book explores these questions, ultimately calling into question the very existence of sex education itself. The analysis is centred on the marginalised lives of sex workers. This focus allows us to see sex education and sex work in a new light and provides insights into the implications of sex education in public schools and teacher education. By considering the relationship between sex education and sex work, Caitlin Howlett reveals the way in which sex education exists as a form of state violence, and continues to maintain close ties to sexism, racism, colonialism, and capitalism. Drawing on Foucauldian genealogy, feminist history, epistemology, post-humanism, and queer of color critique, Howlett calls for an end to sex education as a federally funded project and argues for new pedagogical approaches to educating about sex, gender, and sexuality in schools.